Nature and misuse of non-mandatory non-GAAP (adjusted) earnings by JSE-listed firms - Howard, Michael (My University, 2016)
This research report evaluates the nature of, and gathers evidence of, the potential misuse of the non-GAAP 'adjusted earnings' by JSE-listed firms in South Africa. The prior literature is explored and applied to the South African context which is a unique environment due to the mandatory use of the non-GAAP Headline Earnings . The prior literature provides the grounding for the research methods which enhance the validity of the study. Adjusted earnings are analysed through 3 research questions and sub-questions. The first research question focuses on the nature of the use of adjusted earnings in South Africa, by examining the extent of use of adjusted earnings by a population of JSE firms, as well as the most common types of adjustments used. It is evaluated using descriptive statistical methods from data from databases and company annual financial reports. Research question 2 gathers evidence for misuse through the identification of 'valid' and 'invalid' adjustments made in the determination of adjusted earnings, as well as the identification of the repeated use of particular adjustments, which are indicators of misuse from the prior research of Bhattacharyaa, Black, Christensenb and Larsonc (2003) and Doyle, Lundholm and Soliman (2003). This question uses an ANOVA and repeated measure approach respectively using the same data from research question 1. The third research question examines whether there is an association between adjusted earnings and whether firms meet or beat analyst earnings forecasts more often (the dependent variable) as set out in Doyle, Jennings and Soliman (2013). This is assessed using logistic regression analysis using analyst earnings forecast data and company results data The results indicate that types of firms and adjustments made in South Africa are similar to U.S. literature. It raises questions around use of adjusted earnings as a performance metric and the use of Headline Earnings in South Africa. Evidence of misuse of adjusted earnings was found. In addition, a strong relationship similar to the Doyle et al. (2013) findings was found between the use of upwardly adjusted earnings and the propensity of firms to meet or beat analyst forecasts. Whether a firm s accounting earnings met or beat the forecast was also found to have significant influence on the dependent variable. It was also found that South African firms met or beat analyst forecasts significantly less often than U.S. firms, suggesting that there may be structural differences in the analyst forecasts environment in South Africa when compared to the U.S. The results suggest that adjusted earnings may be misused in South Africa, and one of the motivations to do so is to meet or beat analyst earnings forecasts.
A research report submitted In partial fulfilment of the degree Master of Commerce (Accounting) University of the Witwatersrand
Keywords: Corporations--Valuation--South Africa; Corporations--Accounting; Financial statements--South Africa; Fair value (Accounting)